2019
DOI: 10.1016/j.cnp.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Multinodular and vacuolating neuronal tumor (MVNT): A presumably incidental and asymptomatic case in an intractable epilepsy patient

Abstract: HighlightsMultinodular vacuolating neuronal tumor (MVNT) was initially reported as epilepsy-related brain tumor.MVNT can exist as incidental and asymptomatic lesions in some cases.It is not always necessary to perform surgical resection of MVNT even in patients with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Previously, MVNT with no neurological symptoms was reported in a 60-year-old man [ 6 ]. Additionally, MVNT was reported in a 33-year-old female diagnosed with epilepsy following an episode of limbic encephalitis two years prior [ 5 ]. In that case, the tumor was identified because of the patient’s seizures, localized to the temporal lobe; however, it was concluded that the seizures were unrelated to the MVNT [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, MVNT with no neurological symptoms was reported in a 60-year-old man [ 6 ]. Additionally, MVNT was reported in a 33-year-old female diagnosed with epilepsy following an episode of limbic encephalitis two years prior [ 5 ]. In that case, the tumor was identified because of the patient’s seizures, localized to the temporal lobe; however, it was concluded that the seizures were unrelated to the MVNT [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MVNT was reported in a 33-year-old female diagnosed with epilepsy following an episode of limbic encephalitis two years prior [ 5 ]. In that case, the tumor was identified because of the patient’s seizures, localized to the temporal lobe; however, it was concluded that the seizures were unrelated to the MVNT [ 5 ]. Consistent with the previous reports, our patient’s MVNT showed no change on imaging at three-month, six-month, and one-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation